Improving access to HIV care among people who inject drugs through tele-harm reduction: a qualitative analysis of perceived discrimination and stigma - Carolina Scaramutti; Belén Hervera; Yanexy Rivera; Teresa A. Chueng; David W. Forrest; Edward Suarez; David P. Serota; Hatoun Alkamli; Katrina Ciraldo; Tyler S. Bartholomew; Hansel E. Tookes (Harm Reduction Journal, 2024)
Abstract Background Tele-harm reduction (THR) is a telehealth-enhanced, peer-led, harm reduction intervention delivered within a trusted syringe services program (SSP) venue. The primary goal of THR is to facilitate linkage to care and rapid, enduring virologic suppression among people who inject drugs (PWID) with HIV. An SSP in Miami, Florida, developed THR to circumvent pervasive stigma within the traditional healthcare system. Methods During intervention development, we conducted in-depth interviews with PWID with HIV (n = 25) to identify barriers and facilitators to care via THR. We employed a general inductive approach to transcripts guided by iterative readings of the raw data to derive the concepts, themes, and interpretations of the THR intervention. Results Of the 25 PWID interviewed, 15 were in HIV care and adherent to medication; 4 were in HIV care but non-adherent; and 6 were not in care. Themes that emerged from the qualitative analysis included the trust and confidence PWID have with SSP clinicians as opposed to professionals within the traditional healthcare system. Several barriers to treatment were reported among PWID, including perceived and actual discrimination by friends and family, negative internalized behaviors, denial of HIV status, and fear of engaging in care. Facilitators to HIV care included empathy and respect by SSP staff, flexibility of telehealth location, and an overall destigmatizing approach. Conclusion PWID identified barriers and facilitators to receipt of HIV care through the THR intervention. Interviews helped inform THR intervention development, centered on PWID in the destigmatizing environment of an SSP.